Feeding and oral hygiene habits of preschool children in Pakistan and their caregivers' attitudes - Awais, Faiza; Naheed, Kiran; Shahzad, Hazik B.; Khan, Ayyaz A. (UI Scholars Hub, 2019)
Background: Early childhood caries remains a problem in both developed and developing countries. Several maternal determinants are involved in early caries development. This study aimed to identify feeding and oral hygiene practices associated with childhood caries in Lahore, Pakistan. Methods: A questionnaire-based survey was conducted in paediatric outpatient department of Sheikh Zaid Hospital, from January to March 2016. A total of 435 children aged 12–15 months were enrolled in the study. Results: Children who were fed milk with added sugar, were 30% more likely to have decayed teeth than those fed without sugar. Children who received on demand night-time feeding were 50% more likely to have carious lesions than those who were fed once or twice at night. Children eating sweet snacks multiple times a day were on average 80% more likely to have caries, compared to those who were given sweets once or twice a day. Conclusions: Higher tooth cleaning frequency, and teeth cleaning at night were associated with lower risk of childhood caries, whereas the use of milk with added sugar, on-demand night feeding, and high frequency of sweets taken per day contributed to increased caries. Thus, improved maternal counseling may help prevent early childhood caries in Pakistan.